2017
DOI: 10.5194/angeo-35-999-2017
|View full text |Cite
|
Sign up to set email alerts
|

Electron cyclotron maser instability (ECMI) in strong magnetic guide field reconnection

Abstract: Abstract. The ECMI model of electromagnetic radiation from electron holes is shown to be applicable to spontaneous magnetic reconnection. We apply it to reconnection in strong current-aligned magnetic guide fields. Such guide fields participate only passively in reconnection, which occurs in the antiparallel components to both sides of the guidefield-aligned current sheets with current carried by kinetic Alfvén waves. Reconnection generates long (the order of hundreds of electron inertial scales) electron exha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…There are several possible solutions to this escape problem of radio waves. This could be appropriate mode conversion processes (Treumann & Baumjohann 2017) or the existence of solar coronal flux tubes. According to them, the cutoff frequency (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are several possible solutions to this escape problem of radio waves. This could be appropriate mode conversion processes (Treumann & Baumjohann 2017) or the existence of solar coronal flux tubes. According to them, the cutoff frequency (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Note that our study focuses on a local generation mechanism of type III SRBs due to magnetic reconnection generating superthermal electrons in solar flares. While some aspects of this process have already been investigated previously (Wu et al 2014; Treumann & Baumjohann 2017; Zhou et al 2020), we analysed here the generation mechanisms of fundamental Langmuir and electron cyclotron waves as well as their harmonics when the electron beams propagate through small-scale density gradients in the ambient plasma. We show that density inhomogeneities fundamentally change the properties of the resulting waves.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent paper [1] we suggested that strong-guide field reconnection may play a role in the generation of radiation in the topside auroral ionosphere by the electron cyclotron maser instability mechanism [2][3][4]. This idea was based on the assumption that at the boundary between the upward and downward current regions the magnetic fields of kinetic Alfvén waves might undergo reconnection, causing electron exhausts which are similar to electron holes while being of larger scale.…”
Section: Introductionmentioning
confidence: 99%